Politisasi Agama dan Politik Identitas: Politicization of Religion and Identity Politics - Ridwan, Ridwan; Musafir Pababbari (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Religious politicization is a significant phenomenon in Indonesia's political dynamics, where religious symbols, values, and institutions are utilized for political purposes. This study aims to analyze the impact of religious politicization on Indonesia’s democratic processes, particularly in terms of voter participation, social polarization, and public policy. Additionally, it explores strategies and measures that can be implemented by the government, society, and civil organizations to mitigate the negative effects of religious politicization and create a fair and inclusive election process. Using a qualitative approach with a descriptive-analytical method, the study concludes that religious politicization exacerbates social fragmentation, diminishes trust in political institutions, and shifts focus away from substantive issues. Therefore, collective actions such as political education, campaign regulation, and the promotion of interfaith dialogue are necessary to prevent the exploitation of religion in politics. These efforts are expected to ensure that democracy in Indonesia operates in a healthy and harmonious manner.